Improvement of generalized difference-based mixed Liu estimator in partially linear model. Issue 18 (17th September 2018) - Wu, Jibo
ABSTRACT: In this paper, a generalized difference-based mixed Liu estimator in partially linear model is presented, when it is supposed that the regression parameter may be restricted to a subspace and compare the proposed estimators in the sense of matrix mean squared error criteria. Finally a simulation study is presented to show the performance of the estimators.